2016
DOI: 10.1186/s40749-016-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pulmonary Fibrosis and Emphysema, a clinical review

Abstract: Combined Pulmonary Fibrosis and Emphysema (CPFE) refers to the coexistence of upper lobe predominant emphysema with diffuse pulmonary fibrosis, mainly in the lower lobes. Although initially described in patients with Idiopathic Pulmonary Fibrosis (IPF), since then it has been described in other forms of pulmonary fibrosis, most notably collagen tissue disorder associated interstitial lung diseases. High Resolution Computed Tomography (HRCT) has a pivotal role in diagnosis. Recognizing CPFE is not an academic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…However, DLCO and DLCO/vital capacity were more rapidly reduced in patients with CPFE than in patients with COPD. FEV 1 is usually preserved in patients with CPFE because the traction effects of interstitial fibrosis prevent small airway collapse during expiration [ 12 , 110 ]. However, patients with CPFE involving rapid FEV 1 decline had higher mortality [ 111 ].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DLCO and DLCO/vital capacity were more rapidly reduced in patients with CPFE than in patients with COPD. FEV 1 is usually preserved in patients with CPFE because the traction effects of interstitial fibrosis prevent small airway collapse during expiration [ 12 , 110 ]. However, patients with CPFE involving rapid FEV 1 decline had higher mortality [ 111 ].…”
Section: Managementmentioning
confidence: 99%
“…Pulmonary vasodilator therapy for pulmonary hypertension in patients with CPFE is not recommended, because there is minimal evidence to support this approach [ 145 ]. The usage of pulmonary vasodilators may worsen V/Q mismatch and hypoxemia [ 110 ]. However, a recent case report indicated that the use of tadalafil led to improvements in pulmonary arterial compliance and exercise capacity [ 146 ].…”
Section: Managementmentioning
confidence: 99%
“…Literature so far has exhibited contradicting results regarding the survival of CPFE versus sole IPF patients with some of the studies showing worsened survival [5,6] and other studies showing no difference [7,8] or even improved survival [9,10]. Several reasons could be implicated for the discrepant results of the studies so far [11,12,13]. One of these reasons could be the inclusion in the pulmonary fibrosis group of patients with nonspecific interstitial pneumonia, which has a better prognosis compared to IPF.…”
mentioning
confidence: 66%
“…However, DLCO and DLCO/vital capacity were more rapidly reduced in patients with CPFE than in patients with COPD. FEV1 is usually preserved in patients with CPFE because the traction effects of interstitial fibrosis prevent small airway collapse during expiration 12,109 .…”
Section: Routine Pulmonary Function Testsmentioning
confidence: 99%
“…Pulmonary vasodilator therapy for pulmonary hypertension in patients with CPFE is not recommended, because there is minimal evidence to support this approach 144 . The usage of pulmonary vasodilators may worsen V/Q mismatch and hypoxemia 109 . However, a recent case report indicated that the use of tadalafil led to improvements in pulmonary arterial compliance and exercise capacity 145 .…”
Section: Vasodilators For Pulmonary Hypertensionsmentioning
confidence: 99%